The Life and Death of a Good Idea: Murray Ross's Vision for the "New University". - Grayson, J. Paul (Journal of Canadian Studies)
In Ontario, in the 1960s, several new universities were founded; students flocked to post-secondary institutions in record numbers; and enrolment in arts and science programs reached the highest level since the end of the Second World War. Each of the new universities had its own mandate. As articulated by Murray Ross, its founding president, that of York University was to provide an interdisciplinary education that would contribute to students' personal development, and understanding of the Canadian political system and world in which they lived. This article focuses on the first students to earn a York degree through Glendon College and the extent to which their university experiences and outcomes were consistent with the objectives identified by Ross. An examination of information collected on students at Glendon in the 1960s shows that by and large their reported experiences and outcomes were in keeping with Ross's ideals; however, by the time they graduated, the mandate of the university and college had changed. While liberal arts continued to be important, the main mandate of the college became that of providing a bilingual education.